Hemibrycon guejarensis, a new species from the Güejar river, Orinoco basin, Colombia (Characiformes: Characidae) with a review the populations identified as Hemibrycon metae (Revista de Investigaciones Universidad del Quindío, 2017)
Hemibrycon guejarensis, new species, is described from the Güejar River, La Macarena mountain range, upper Guaviare River drainage, Colombia. The new species is distinguished from most cis-Andean congeners (H. jabonero Lake Maracaibo and adjacent Caribbean drainages, H. metae which is found in the Guavio River, some Orinoco and Caribbean River drainages in Venezuela, and H. taeniurus from Trinidad and adjacent mainland drainages in Venezuela) in having ii, 7, i dorsal-fin rays (vs. ii, 8). H. guejarensis is further distinguished from H. taeniurus and H. jabonero, in having a wider second pigment layer in the humeral spot (covering 3 vs. 2 scale widths). H. guejarensis is very similar to H. metae (an allopatric species also present in streams of the Orinoco River Basin in Venezuela and Colombia and some Venezuelan Caribbean drainages). Hemibrycon guejarensis is distinguishedby the orientation of the dorsal lateral-line canal which crosses the ventral part of the humeral spot transversely vs. horizontally across dorsal part of spot in the holotype of H. metae and Orinoco and Caribbean populations. H. guejarensis differs from H. metae in having the tip of the pectoral fin passing the pelvic-fin insertions (vs. pectoral fin tip not reaching pelvic-fin insertions). We identify populations previously considered as Hemibrycon metae from Venezuelan Orinoco River Basin piedmont streams and Caribbean drainages to be instead H. jabonero and H. taeniurus. Careful analysis of these populations indicated that all of them differ from the H. metae holotype and topotypic specimens in pelvic fin and postorbital lengths.
Keywords: Fishes; Teleostei; Stevardiinae; Taxonomy; South America